Chemical composition and pasting properties of tapioca grits from different cassava varieties and roasting methods - Adebowale, A.A.; Sanni, Lateef O.; Onitilo, M.O. (2008)
This study investigated the chemical composition and pasting properties of tapioca grits from different cassava varieties and roasting methods. Tapioca grits (partially gelatinized irregular flakes from roasted cassava starch), were produced from three different cassava varieties (Odongbo, TMS 30572 and Oko-iyawo) and two roasting methods (traditional and rotary dryer). The chemical composition and pasting properties of the tapioca grits were evaluated. The results showed that the effect of cassava variety and roasting methods on chemical composition of tapioca grits was significantly different (P<0.05). The principal component analysis (PCA) of variation in the chemical properties of the tapioca grits indicated that moisture, sugar and starch accounted for 83% of the variation in the chemical properties of tapioca grits. This study showed that peak and hot paste viscosities are the key pasting parameters in characterizing tapioca grits from the cassava varieties and roasting methods studied and that variation in peak viscosity of the tapioca grits might be due more too varietal influence than the roasting method.